INTERITAS SEBAGAI PEMODERASI PENGARUH KOMITMEN ORGANISASI PADA KINERJA AUDITOR - Ananta Wijana, Dewa Gde; Ramantha, I Wayan (E-Jurnal Akuntansi; Vol 10 No 3 (2015), 2015)
This study aims to determine "Integrity As a moderating Effect of Organizational Commitment in Performance Auditor (Studies in Public Accounting Firm in Bali)". The research was conducted on the entire public accounting firm in Bali. Sampling technique used this study was stratified random sampling. D ata collection methods used were questionnaire and documentation methods. While the data analysis technique used is the technique of multiple linear regression analysis. The results of this study demonstrate the organization's commitment and significant positive effect on the performance of auditors. Integrity proved to moderate the relationship of organizational commitment in the performance of auditors.
Keywords: auditor performance, organizational commitment, integrity.